Advanced calculus - Nickerson, H. K. 1918- (Helen Kelsall); Spencer, D. C. 1912-2001. (Donald Clayton); Steenrod, Norman Earl, 1910-1971. (Mineola, N.Y. : Dover Publications, 2011)
"Classroom-tested in a Princeton University honors course, this text offers a unified introduction to advanced calculus. Starting with an abstract treatment of vector spaces and linear transforms, the authors present a corresponding theory of integration, concluding with a series of applications to analytic functions of complex variables. 1959 edition"--
Originally published: Princeton, N.J. : D. Van Nostrand, 1959.
Includes bibliographical references.
Keywords: Calculus; Vector analysis; MATHEMATICS / Calculus